Field evaluation of the combination of lincomycin and spectinomycin for the treatment of contagious agalactia of sheep and goats - ΣΠΑΗΣ Α. Γ.; ΑΡΓΥΡΟΥΔΗΣ Σ.; ΣΑΡΡΗΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The combination of the antibiotics lincomycin and spectinomycin was tested in 4 flocks, 3 with goats and 1 with sheep, suffering from natural Contagious Agalactia. A serie of 3 intramuscular injections, once daily, of 5mg/kg b.w. of lincomycin and 10mg/kg b.w. spectinomycin, was used. From the results of this study it is concluded that the combination of the above two antibiotics is effective for the treatment of Contagious Agalactia. The effectiveness with full recover of the sick animals, depending from various factors (duration of disease, localisations, productive period etc.), was estimated from 55% up to 80%. The drug proved more effective when used in the acute forms of the disease